Optimisasi Penggunaan Energi Listrik Pada Unit Pengolahan Air Minum Selat Panjang - ., Suparno (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstract Optimization of the annual energy cost of a pumping station at the drinking water company can increase profits and improve the competitiveness of enterprises. This optimization model is a non-linear program which consists of three characteristic equations, namely the piping systems, pump and the annual load . This model can be used to evaluate the performance of a pumping station and choose the most efficient pump specification by setting discharge using a variable speed drive equipment. Implementation of the program on Selat Panjang drinking water processing installations unit with real data that exist in the field indicated that, the performance of the existing system installation is less efficient. Pump replacement with a more suitable specification based on the results of program implementation and installation of variable speed drives with closed-loop control actions can save energy by more than 25% of the previous conditions. Keywords Energy Saving, Pumps, Efficiency, Variable Speed Drives.